Why live recording sounds better: a case study of Schumann's Träumerei - Shoda, Haruka; Adachi, Mayumi (Frontiers in Psychology, 2015)
We explore the concept that artists perform best in front of an audience. The negative effects of performance anxiety are much better known than their related cousin on the other shoulder: the positive effects of "social facilitation." The present study, however, reveals a listener's preference for performances recorded in front of an audience. In Study 1, we prepared two types of recordings of Träumerei performed by 13 pianists: recordings in front of an audience and those with no audience. According to the evaluation by 153 listeners, the recordings performed in front of an audience sounded better, suggesting that the presence of an audience enhanced or facilitated the performance. In Study 2, we analyzed pianists' durational and dynamic expressions. According to the functional principal components analyses, we found that the expression of "Träumerei" consisted of three components: the overall quantity, the cross-sectional contrast between the final and the remaining sections, and the control of the expressive variability. Pianists' expressions were targeted more to the "average" of the cross-sectional variation in the audience-present than in the audience-absent recordings. In Study 3, we explored a model that explained listeners' responses induced by pianists' acoustical expressions, using path analyses. The final model indicated that the cross-sectional variation of the duration and that of the dynamics determined listeners' evaluations of the quality and the emotionally moving experience, respectively. In line with human's preferences for commonality, the more "average" the durational expressions were in live recording, the better the listeners' evaluations were regardless of their musical experiences. Only the well-experienced listeners (at least 16 years of musical training) were moved more by the "deviated" dynamic expressions in live recording, suggesting a link between the experienced listener's emotional experience and the unique dynamics in music.